IMPLEMENTASI ASAS KEJELASAN DALAM PENYUSUNAN PERATURAN PERUNDANG-UNDANGANPASCA UU 13/2022 - Muhammad Arief Hidayatullah; Mutiara; Akhmad Zaki Yamani (Yayasan Pendidikan Literasi Borneo, 2026)
This research examines the implementation of the principle of clarity in formulation within the legislative process following the introduction of Law Number 13 of 2022, which serves as the second amendment to Law Number 12 of 2011. The principle of clarity in formulation is regarded as a crucial tenet aimed at establishing legal certainty through the employment of legal language that is clear, systematic, and devoid of ambiguity that could lead to multiple interpretations. The methodology employed in this study is a normative legal research method, utilizing both a statutory and a conceptual approach. The findings reveal that, despite enhancements made to the provisions concerning the principle of clarity in formulation, its execution continues to encounter various obstacles, including the presence of norms that are open to multiple interpretations, insufficient regulatory harmonization, and disparities in the quality of norm drafting. Consequently, it is deemed essential to enhance the competence of regulatory drafters and to reinforce regulatory harmonization in order to produce high-quality legislation.